Analysis of Cognitive Biases in Construction Health and Safety in New Zealand - Mahesh Babu Purushothaman; Pricilia Jessica; Funmilayo Ebun Rotimi (Buildings)
The construction industry’s complexity and high-risk nature present significant decision-making challenges, often resulting in errors that jeopardise health and safety performance. Cognitive biases can further distort risk assessments and influence decision-making, ultimately affecting safety behaviours and outcomes. Although numerous studies have explored cognitive biases in construction, there remains a lack of a comprehensive understanding regarding how these biases interact with key decision factors related to health and safety. This study aimed to advance sustainable health and safety practices within the construction industry by examining the consequences and interplay of cognitive biases and essential decision factors through a systematic literature review. Two hundred and eighty-three articles published between 2018 and 2024 were analysed, with forty-five selected for inclusion. The network analysis findings identify key decision factors, reinforcing loops, and critical paths that affect health and safety performance, illustrating how cognitive biases influence risk perception, decision complexity, and workplace safety behaviours. The insights gained from this study highlight the challenges and the potential for improvement. They serve as a foundation for researchers, construction safety professionals, and policymakers to develop targeted interventions that mitigate cognitive biases, enhance risk perception, and strengthen decision-making frameworks, ultimately improving health and safety performance in the construction sector.